ANALISIS ISI BUKU TEKS PELAJARAN SOSIOLOGI MENGGUNAKAN TAKSONOMI BLOOM DI SMAN 1 UNGGULAN INDRALAYA UTARA - Fitri, Fitri; Alfitri, Alfitri (Jurnal ENTITAS SOSIOLOGI, 2019)
This study aims to discuss the contents of textbooks on sociology subjects at the high school level. This study uses descriptive qualitative methods. Data collection techniques are carried out through observation, interviews and literature. The data analysis technique used is content analysis, namely the researcher reads and develops the sociology textbooks written by Srikandi four. The results of the study showed that the contents of the sociology textbooks written by Srikandi four were more dominant in the cognitive domain (knowledge).  Keywords: Text Textbooks, Sociology, Blom Taxonomy